U.S. trade threats: rhetoric or war? - Kherallah, Mylene; Beghin, John C. (Wiley, 1998)
We present an empirical analysis of factors determining trade wars and agreements under U.S. trade law Section 301. A system of two probit equations is estimated using historical data on Section 301 cases to determine which economic and political factors increase the likelihood of trade frictions. The likelihood of trade war increases when the United States's export share in the world market declines, when the United States is less dependent on the market of the targeted country, when foreign policy makers are in an election year, and when negotiations relate to highly protected and unionized industries in the targeted country.